Valorization of spent shiitake substrate for recovery of antitumor fungal sterols by ultrasound‐assisted extraction. Issue 5 (5th August 2018) - Wang, Qi; Cheng, Junxia; Wang, Lixia; Yan, Shuaishuai; Wang, Ruiqin; Zhang, Haisheng; Shao, Hongjun; Yang, Xingbin
Abstract: The ongoing expansion of mushroom industries has generated enormous spent mushroom substrate with the potential for production of valuable chemicals. This study aimed to investigate ultrasound‐assisted extraction (UAE) of fungal sterols from spent shiitake ( Lentinula edodes ) substrate (SSS) by response surface methodology. The results showed that three variables, including ultrasonic power, extraction time, and liquid–solid ratio, had considerable influence on the extraction efficiency of total fungal sterols with liquid–solid ratio being highly significant for the process. The optimal UAE conditions included liquid–solid ratio 22 mL/g, ultrasonic power 432 W, and extraction time 16 min for the maximum recovery of fungal sterols (151.62 mg ergosterol equivalents/100 g dry weight) from SSS. Further GC‐MS analysis indicated that the extracts yielded under the optimal conditions contained ergosterol, ergosta‐7, 22‐dienol, and β‐sitosterol, in which ergosterol was the most abundant mycosterol. The extracts also showed a comparable antitumor effect against three cancer cell lines. Practical applications: Spent mushroom substrate, a major by‐product of mushroom industries, remains a big challenge for the profitability of mushroom industries. Our results indicated that spent shiitake substrate can be valorized by UAE for production of fungal sterols.